2021
DOI: 10.1080/10426914.2021.1942909
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized material production via multi-stack Upward Friction Stir Processing (UFSP)

Abstract: An innovative friction stir processing variant, named Upward Friction Stir Processing (UFSP), for producing customized materials with multifunctional particles is presented. In the UFSP, an upward flow is used to disperse these functional particles in a metallic matrix, in opposition to the widely used downward flow. As a proof of concept, SiC particles were introduced and dispersed into an aluminium alloy AA7075-T651 matrix to study different process parameters and to validate this novel material processing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The results showed that variations in microhardness values across the three planes were not significant and that AA6082-T651 had an average hardness of 118 HV0.5. The characterization of the other metallic alloy (AA 7075-T651) was carried out by the authors in previous works [42,43]. Table 2 shows the mechanical, electrical, and thermal properties of the two base materials used in this work.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that variations in microhardness values across the three planes were not significant and that AA6082-T651 had an average hardness of 118 HV0.5. The characterization of the other metallic alloy (AA 7075-T651) was carried out by the authors in previous works [42,43]. Table 2 shows the mechanical, electrical, and thermal properties of the two base materials used in this work.…”
Section: Methodsmentioning
confidence: 99%
“…The SiC particles had nonuniform shapes and sizes ranging between 4 and 20 µm, with an average diameter of Coatings 2023, 13, 962 4 of 18 6 µm [45]. Figure 1 shows the morphology and dimensions of the SiC particles observed through scanning electron microscopy (SEM) [42]. During the experimental tests, reinforcement particles were incorporated onto the surface of the metallic alloys to produce a surface composite.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, FSP parameters (tool rotation and transverse speeds, tilt angle, tool geometries, etc.) are the other major influencing factors controlling surface composites' final microstructure and properties [25][26][27]. The tool rotation speeds from 400 to 2000 rev min −1 and transverse speed from 20 to 100 mm min −1 during FSP are commonly used for Mg alloys.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24]. Recently, a novel FSP technique (upward FSP) has been introduced with the successful processing of SiC particles into an aluminium alloy (AA7075-T651) [25]. The processed matrix exhibited more uniform dispersion of foreign particles.…”
Section: Introductionmentioning
confidence: 99%